The achievement of the 5th mdg: regional differences in Colombia (2012)
Colombia’s maternal and child health has improved over the past 40 years. However, the maternal mortality rate (MMR) is still higher than in other developing countries, and consequently the 5th Millennium Development Goal (MDG) of decreasing the MMR by three quarters, will not be reached.